The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2017
DOI: 10.1371/journal.pone.0174980
|View full text |Cite|
|
Sign up to set email alerts
|

Influenza A H5N1 and H7N9 in China: A spatial risk analysis

Abstract: BackgroundZoonotic avian influenza poses a major risk to China, and other parts of the world. H5N1 has remained endemic in China and globally for nearly two decades, and in 2013, a novel zoonotic influenza A subtype H7N9 emerged in China. This study aimed to improve upon our current understanding of the spreading mechanisms of H7N9 and H5N1 by generating spatial risk profiles for each of the two virus subtypes across mainland China.Methods and findingsIn this study, we (i) developed a refined data set of H5N1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 81 publications
1
17
0
Order By: Relevance
“…To construct strategies to control diseases, the identification of timely risk factors in outbreaks is important (Lewallen & Courtright, 1998). Previous avian influenza epidemiologic studies have identified several risk factors from a variety of settings and countries (Abbas, Wilking, Horeth-Bontgen, & Conraths, 2012;Arriola et al, 2015;Beaudoin et al, 2014;Biswas et al, 2011;Boender et al, 2007;Bui, Gardner, MacIntyre, & Sarkar, 2017;Cao et al, 2010;Chaudhry, Rashid, Thrusfield, Welburn, & Bronsvoort, 2015;Desvaux et al, 2011;Dinh et al, 2006;Fang et al, 2008;Fasina, Rivas, Bisschop, Stegeman, & Hernandez, 2011;Gale et al, 2014;Garber et al, 2016;Gilbert et al, 2006;Henning et al, 2009;Huang, Zeng, & Wang, 2016;Iglesias, Jesus Munoz, Martinez, & de la Torre, 2010;Kung et al, 2007;Liu et al, 2015;Lohiniva et al, 2013;Loth, Gilbert, Osmani, Kalam, & Xiao, 2010;Mannelli, Ferre, & Marangon, 2006;Martin et al, 2011;McQuiston et al, 2005;Metras et al, 2013;Mounts et al, 1999;Musa, Abdu, Sackey, & Oladele, 2013;Nishiguchi et al, 2007;Osmani et al, 2014;Paul et al, 2011;Tenzin, Wangdi, & Rai, 2017;Thomas et al, 2005;Thompson, Sinclair, & Ganzevoort, 2008;…”
Section: Introductionmentioning
confidence: 99%
“…To construct strategies to control diseases, the identification of timely risk factors in outbreaks is important (Lewallen & Courtright, 1998). Previous avian influenza epidemiologic studies have identified several risk factors from a variety of settings and countries (Abbas, Wilking, Horeth-Bontgen, & Conraths, 2012;Arriola et al, 2015;Beaudoin et al, 2014;Biswas et al, 2011;Boender et al, 2007;Bui, Gardner, MacIntyre, & Sarkar, 2017;Cao et al, 2010;Chaudhry, Rashid, Thrusfield, Welburn, & Bronsvoort, 2015;Desvaux et al, 2011;Dinh et al, 2006;Fang et al, 2008;Fasina, Rivas, Bisschop, Stegeman, & Hernandez, 2011;Gale et al, 2014;Garber et al, 2016;Gilbert et al, 2006;Henning et al, 2009;Huang, Zeng, & Wang, 2016;Iglesias, Jesus Munoz, Martinez, & de la Torre, 2010;Kung et al, 2007;Liu et al, 2015;Lohiniva et al, 2013;Loth, Gilbert, Osmani, Kalam, & Xiao, 2010;Mannelli, Ferre, & Marangon, 2006;Martin et al, 2011;McQuiston et al, 2005;Metras et al, 2013;Mounts et al, 1999;Musa, Abdu, Sackey, & Oladele, 2013;Nishiguchi et al, 2007;Osmani et al, 2014;Paul et al, 2011;Tenzin, Wangdi, & Rai, 2017;Thomas et al, 2005;Thompson, Sinclair, & Ganzevoort, 2008;…”
Section: Introductionmentioning
confidence: 99%
“… 3 , and Bui et al . 18 provided detailed descriptions on the temporal, spatial, and population distributions of the epidemics. These studies laid the foundation for investigating the epidemiological characteristics of the H7N9 epidemics.…”
Section: Discussionmentioning
confidence: 99%
“…Instead of predicting whether it exists or not, Maxent estimates the relative environmental adaptability of species existence [14].…”
Section: Ecological Niche Model Construction and Evaluationmentioning
confidence: 99%